Comparison of intramyometrial and intramuscular 15 methyl PGF2? against traditional prophylactic intramuscular methergin for the active management of third stage of labor - Shrestha, Anju; Urala, MS; Upreti, Dhurba; Niraula, Surya (Nepal Journal of Obstetrics and Gynaecology, 2014)
Objective: To compare intramyometrial, intramuscular (I M) 15 methyl PGF2α with IM Methergin on the duration and blood loss of 3rd and 4th stage of labor. Method: Prospective randomized control study, done from May 2004 to June 2005. Three hundred parturient women were randomly assigned to receive either an intramyometrial or IM 15 methyl PGF2α or IM methergin immediately after delivery of baby. Duration of 3rd stage and blood loss during 3rd and 4th stage of labor was measured. Other parameters measured were – presence of atonic postpartum hemorrhage (PPH), need for MRP, and blood transfusion, any side effects of drugs. Results: Women who received prophylactic intramyometrial PGF2α had significantly shorter duration of 3rd stage of labor (2.3 + 0.66 mins: p= 0.0000) compared to both IM group ( 3.04+1.03 mins) and IM methergin group ( 4.22+ 1.58 mins) and also significantly less blood loss ( median- 110ml; P= 0.0002) compare to both IM group (median-145ml) and IM methergin group( medin-197ml). Conclusion: Intramyometrial PGF2α is better than IM PGF2α and methergin in terms of reducing duration of 3rd stage and blood loss. Thus can be prophylactically used especially in those patients where even minimal blood loss will adversely affect the health of mother. DOI: http://dx.doi.org/10.3126/njog.v3i2.10829 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 35-39